2020
DOI: 10.1080/17441692.2020.1805788
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of male partner engagement policies on HIV care-seeking in three African countries: Findings from the SHAPE UTT study

Abstract: We explored how strategies to promote male partner engagement influenced HIV care-seeking among men and women living with HIV. Indepth interviews were conducted with 25 health workers, 66 female service users and 10 male partners in Ifakara (Tanzania), Karonga (Malawi) and uMkhanyakude (South Africa) to elicit experiences of offering, providing or receiving HIV care in the context of antenatal care. Data were coded inductively and analysed thematically. Participants reported benefits of couple testing during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Our study supports others in raising questions about whether male engagement is being used to its full advantage of bringing in men as partners in maternal health [19]. Several women in our study expressed dissatisfaction with the extent to which their partners were engaged in their ANC.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our study supports others in raising questions about whether male engagement is being used to its full advantage of bringing in men as partners in maternal health [19]. Several women in our study expressed dissatisfaction with the extent to which their partners were engaged in their ANC.…”
Section: Discussionsupporting
confidence: 79%
“…These unintended consequences could outweigh the benefits that male engagement in ANC is meant to offer. This study adds to evidence that the implementation of male engagement in ANC in Tanzania could create inequities in care and disadvantage women who are not in stable relationships [19,20,22,30].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…There are substantial gaps in HIV service use and coverage for men and boys in South Africa [ 7 ]. There is evidence to suggest that, overall, men have lower levels of engagement and retention in HIV care [ 8 , 9 ] and higher mortality on ART than women [ 10 ]. The observed differences in mortalities may be best explained by background differences in mortality between men and women may be related to other factors including men’s poor usage of facility-based health services.…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth article Dube and colleagues examined the consequences of male partner engagement in the context of Option B+ in the three countries (Dube et al, 2020). They reported that couple's testing facilitated HIV status disclosure and promoted HIV care-seeking.…”
mentioning
confidence: 99%